(untitled) (Sains Humanika, 2014)
Nowadays within the era of new technology and knowledge, the worldwide becomes more knowledge oriented. Despite the growing significance of knowledge sharing practices for university success and competitiveness, several barriers make it difficult for knowledge sharing to achieve the goals of universities to deliver innovation and improve the social and cultural enterprise. This paper highlights the barriers that affect knowledge sharing among academic staff in Malaysian universities, categorizing them into two main domains of recently published works, the first domain is the internal barriers and second domain is the external barriers. This review of knowledge sharing barriers amongÂ academic staff provide the university management a starting point to evaluate their situation, towards achieving the vision of 2020 and one of the most important objectives for the Ministry of Higher Education (MOHE) in Malaysia.Â Â